Social issues in children picturebook apps and their reception by the parents of children in early education - Małgorzata Cackowska; Michał Zając (Problemy Wczesnej Edukacji)
The aim of the paper was to assess the growing interest – among both the general public and academia – in the phenomenon of picturebook apps, i.e. products for children dedicated to mobile devices with touchscreens. As the object of interest 4 picturebook apps were chosen, which in different ways present topics connected with social issues (exclusion, sexuality, “otherness”). A selected sample of pre-school children parents were presented with the apps and then interviewed (qualitative research) in order to collect their opinions regarding both the apps and the topics raised in their content. The acquired data documents different attitudes towards the apps – ranging from very open to close minded.